2009
DOI: 10.1097/nmd.0b013e3181aacc08
|View full text |Cite
|
Sign up to set email alerts
|

Does the Form or the Amount of Exposure Make a Difference in the Cognitive-Behavioral Therapy Treatment of Social Phobia?

Abstract: Exposure is considered to be an essential ingredient of cognitive-behavioral therapy treatment of social phobia and of most anxiety disorders. To assess the impact of the amount of exposure on outcome, 30 social phobic patients were randomly allocated to 1 of 2 group treatments of 8 weekly sessions: Self-Focused Exposure Therapy which is based essentially on prolonged exposure to public speaking combined with positive feedback or a more standard cognitive and behavioral method encompassing psychoeducation, cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…Ideally, future studies would include both social and non-social incentives, and reward and punishment trials. Another avenue for future research would be investigating whether the proposed motivational imbalance “shifts or normalizes” after a treatment which successfully increases reward sensitivity (e.g., Borgeat et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, future studies would include both social and non-social incentives, and reward and punishment trials. Another avenue for future research would be investigating whether the proposed motivational imbalance “shifts or normalizes” after a treatment which successfully increases reward sensitivity (e.g., Borgeat et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to support the effectiveness of exposure therapy alone [389,392], however the efficacy of exposure alone compared with CBT is equivocal in the current treatment literature [392-395]. …”
Section: Social Anxiety Disordermentioning
confidence: 99%
“…In social phobia, what helps beyond exposure remains matter of debate and research. Among the usual components of CBT, more exposure appears related to more rapid positive cognitive changes while cognitive work was shown to contribute to more persistent decrease of social avoidance (Borgeat et al, 2009). Some unpublished pilot case studies of our group had indicated that social phobic patients making limited progress in CBT could respond to augmentation by preconscious priming.…”
Section: Introductionmentioning
confidence: 99%